STRATEGY FOR INCREASING THE EFFICIENCY OF PILGRIMAGE TOURISM BASED ON MARKETING RESEARCH - Ortigaliev Azamat Abdumalik ugli; Saidvali Shukrullaevich Yusupov (The Conference Hub, 2025)
This thesis examines the strategy for increasing the effectiveness of pilgrimage tourism based on marketing research. It highlights the need to radically improve the system of providing tourism services to increase tourism potential, measures to further increase the potential of domestic and foreign tourism, the need to develop a comprehensive action plan to address the main problems in the tourism sector, and other issues.
Keywords: Marketing research, strategy, efficiency of pilgrimage tourism, tourism services, domestic and foreign tourism, tourism potential.